Bioavailability of synthetic and biosynthetic deuterated lycopene in humans - Tang, G. W.; Ferreira, ALA; Grusak, M. A.; Qin, J.; Dolnikowski, G. G.; Russell, R. M.; Krinsky, N. I. (Elsevier B.V., 2005)
Current knowledge of the bioavailability of lycopene in humans is limited due to the inability to distinguish newly administered lycopene from the body reserves of lycopene. A quantitative method to assess the absorption and relative bioavailability of newly absorbed synthetic or natural lycopene was developed using two deuterated lycopene sources, in conjunction with an advanced LC/APCI-MS (liquid chromatography/atmospheric pressure chemical ionization-mass spectrometry) to analyze newly absorbed lycopene in blood samples of study subjects. Two subjects (1 male and 1 female) consumed hydroponically grown tomatoes containing deuterium-enriched lycopene (8084 g wet weight tomato containing 16.3 and 17.4 mu mol lycopene, respectively) and two subjects (1 male, and 1 female) consumed 11 mu mol synthetic H-2(10) lycopene in 6 g of corn oil. Tomatoes were steamed and pureed. The doses were given together with a liquid formulated drink with 25% energy from fat. Our results showed that up to 34 days after taking an oral 2 1110 lycopene dose (synthetic or from tomato) with a liquid formula drink, the area under the curve of the average serum percent enrichment response of synthetic lycopene reached 33.9 (+/- 1.7) nmol-day/mu mol lycopene in the dose, whereas that of lycopene from the tomato dose was 11.8 (+/- 0.3) nmol-day/mu mol lycopene in the dose. Our study provides evidence that the absorption of physiological levels of lycopene in intrinsically labeled tomatoes can be studied in humans. From these preliminary investigations, we find that the bioavailability of synthetic lycopene in oil appears to be about three times higher than that of lycopene from steamed and pureed tomatoes. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: lycopene; mass spectrometry; stable isotope; intrinsic labeling; blood response